BARISAN SIMBOL DAN UKURAN INVARIAN FUNGSI MONOTON SEPOTONG-SEPOTONG KONTINU - Kristina Ningrum, Rinurwati (MATEMATIKA, 2011)
. Let Â is piecewise continuous monotone function. In this paper we going to construct g-invariant measure from piecewise continuous monotone function g using minus symbol sequences and plus symbol sequences. This space is generalization from invariant measure piecewise linear transformation